UMPSA appreciates and remembers pensioner services - Nor Salwana, Mohammad Idris (UMPSA, 2024)
PEKAN, 18 December 2023 - Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Dato’ Ts. Dr. Yuserrie Zainuddin presented a certificate of appreciation and retirement to Senior Manager, Management Services Division, Hajah Sabarehan Haji Ismail.